The ISSN International Centre and its Network: A brief Introduction - Béquet, Gaëlle (Access: An International Journal of Nepal Library Association, 2023)
The article recalls the rationale behind the creation of the ISSN international center placed under the dual auspices of the United Nations Educational, Scientific and Cultural Organization (UNESCO) and the International Organisation for Standardisation (ISO).It describes the recent progress achieved by the ISSN International Centre, particularly regarding the openness and quality of ISSN data. The objectives of the Centre's current strategic plan are detailed.